MEDICAL AND NURSING SERVICES AND PATIENTS' SATISFACTION LEVEL - M. Seidi; A. Hydary; S.R. Reis Karami (Iran University of Medical Sciences, 2005)
Patients ' satisfaction is a complex phenomenon which is affected by different factors. Managers and care givers have to be aware of patients ' opinion about their services. Promoting quality of care depends on this issue.   To assess the satisfaction level of patients in medical surgical wards, we conducted a cross-sectional study in which 400 patients, selected by convenient sampling method. The data were collected by interviewing and completing questionnaires.   Findings revealed that 79% of patient were satisfied with services gained from physicians and 74% of them said that they were satisfied with nursing services.   To sum up, promoting the satisfaction level of patients, we recommend perposful considerations and interventions.